Singular perturbation for nonlinear boundary-value problems - Rina Ling (International Journal of Mathematics and Mathematical Sciences)
Asymptotic solutions of a class of nonlinear boundary-value problems are studied. The problem is a model arising in nuclear energy distribution. For large values of the parameter, the differential equations are of the singular-perturbation type and approximations are constructed by the method of matched asymptotic expansions.